2012
DOI: 10.1177/0883073811426502
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmoplegic “Migraine” or Recurrent Ophthalmoplegic Cranial Neuropathy

Abstract: Ophthalmoplegic migraine is a poorly understood neurologic syndrome characterized by recurrent bouts of head pain and ophthalmoplegia. By reviewing cases presenting to our centers in whom the phenotype has been carefully dissected, and systematically reviewing all published cases of ophthalmoplegic migraine in the magnetic resonance imaging (MRI) era, this review sets out to clearly define the syndrome and discuss possible etiologies. We found that in up to one-third of patients, the headache was not migrainou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
3
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(171 citation statements)
references
References 51 publications
4
152
3
12
Order By: Relevance
“…This clinical condition should not be attributed to another disorder such as tumor, infection, and aneurysm. Thrombosis must have been excluded by appropriate imaging (1,5). Recurrent painful ophthalmoplegic neuropathy is a diagnosis of exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This clinical condition should not be attributed to another disorder such as tumor, infection, and aneurysm. Thrombosis must have been excluded by appropriate imaging (1,5). Recurrent painful ophthalmoplegic neuropathy is a diagnosis of exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, oral steroids may be of possible benefit in treating acute exacerbations based on available observational data. Because recurrent painful ophthalmoplegic neuropathy is not a variant of migraine, migrainespecific acute and preventive therapies probably do not have a role in treatment (5). Contrast-enhanced MRI is a useful adjunct in the diagnosis and monitoring response to treatment of recurrent painful ophthalmoplegic neuropathy with oculomotor nerve involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still debated whether an uncontrolled migraine or an oculomotor neuropathy is the primary cause of OM. Some authors suggested the name of ''recurrent painful oculomotor neuropathy'' and suggested recurrent demyelination as the presumed etiology [41]. In three quarters of the Fig.…”
Section: Ophthalmoplegic Migraine (Om)mentioning
confidence: 99%
“…It has recently been proposed that this is not in fact a migraine but instead a demyelinating disorder. 13 Benign paroxysmal vertigo is usually a toddler affliction, and typical attacks are characterised by suddenonset ataxia causing immobility and falls. The affected child looks frightened and pale and may vomit.…”
mentioning
confidence: 99%